Hybrid and Flexible Work Arrangements: A PRISMA 2020 Systematic Literature Review of Drivers, Mechanisms, and Organizational Outcomes - Loso Judijanto; Abdul Muiz (West Science Business and Management, 2026)
The transformation of workplace structures in the digital era has accelerated the adoption of hybrid and flexible work arrangements across organizations worldwide. This study aims to systematically review existing research on hybrid and flexible work models by identifying the driving factors, implementation mechanisms, and organizational impacts associated with these work systems. The research employs a Systematic Literature Review (SLR) approach using the PRISMA 2020 framework to ensure a transparent and structured review process. The data were collected from the Scopus database, and a total of 22 peer-reviewed articles were selected through stages of identification, screening, eligibility assessment, and inclusion. The findings indicate that the adoption of hybrid and flexible work arrangements is primarily driven by technological advancement, organizational digital transformation, employee demand for work–life balance, and external environmental pressures such as the COVID-19 pandemic. In terms of implementation mechanisms, organizations rely heavily on digital collaboration technologies, adaptive leadership practices, trust-based management systems, and supportive organizational cultures to sustain hybrid work environments. The review also reveals several organizational impacts, including increased employee productivity, improved job satisfaction, enhanced organizational resilience, and greater talent retention. However, challenges such as communication barriers, employee isolation, and difficulties in performance monitoring remain important issues that organizations must address.